The effect of biogas slurry and mineral fertilizers on growth indicators and productivity of Maize (Zea Mays L.) - كبيبو , عيسى; الزعبي, محمد; أحمد, سقراط (Latakia University Journal -Biological Sciences Series, 2021)
Biogas slurry that resulting from anaerobic digestion of agricultural waste contains plant nutrients and organic matter, therefore, it increases the productivity of crops, improve the soil physical and chemical properties, reduce the harmful effects resulting from excessive mineral fertilizers use and disposal of organic waste in an environmentally friendly way. A field experiment by cultivating hybrid yellow maize (Ghouta 82) was conducted in the Agricultural Scientific Research Center in Tartous Governorate, aiming to reaching the best fertilizing formula with the highest rate of vegetative growth and total plant productivity in low-fertility loamy soil by using biogas and mineral fertilizers. The experiment was carried out according to the random block design by using 11 treatments and 3 replications, the treatments were three levels of biogas slurry (10, 15 and 20 litter/m2) and three levels of mineral fertilizers (25, 50 and 75%) of the fertilizer recommendation for the yellow corn. The results showed a significant increase in plant height and leaf area by applying biogas slurry at rate of (15, 20 litter/m2). Meanwhile significant increase in the plant wet and dry weight when applying biogas slurry at rate of (20 litter/m2) with 50% of the recommended fertilizer dose. Also, the application of biogas slurry at rate of (20 litter/m2) with the second and third levels of mineral fertilizers resulting increase in productivity by more than 90% compared to the control, so the study demonstrated the possibility of using biogas slurry as a supplementary fertilizer and 50% of mineral fertilizers can be replaced with biogas fertilizers.